2012
DOI: 10.1021/ja304410x
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Mediated Fluorination of Aryl Iodides

Abstract: The synthesis of aryl fluorides has been a topic of considerable interest because of the importance of aryl fluorides in pharmaceuticals, agrochemicals and materials. The stability, reactivity and biological properties of aryl fluorides can be distinct from those of the corresponding arenes. Methods for the synthesis of aryl fluorides, however, are limited. We report the conversion of a diverse set of aryl iodides to the corresponding aryl fluorides. This reaction occurs with a cationic copper reagent and silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
124
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(128 citation statements)
references
References 32 publications
3
124
0
1
Order By: Relevance
“…By switching the solvent from acetonitrile to benzonitrile,t he yield was increased to 67 %( entry 2), whereas other solvents provided only trace amounts of 3aa with unexpected 1,4-diphenylbuta-1,3-diyne as the major product by the homocoupling of 1a (entries 3-6). An extensive screening of nitrogen sources (entries 7-11), ligands (entries 12-16), [18] temperature (entries 17 and 18), copper loading (entry 19), additives (entries 20 and 21), and the atmosphere (entries 22 and 23) revealed that the use of two equivalents of Cu(NO 3 ) 2 ·3 H 2 Oinbenzonitrile at 60 8 8Cunder nitrogen atmosphere using tert-butylnitrile (2.0 equiv) as an additive provides the most suitable conditions and afforded 3aa in 83 %yield.…”
Section: Methodsmentioning
confidence: 99%
“…By switching the solvent from acetonitrile to benzonitrile,t he yield was increased to 67 %( entry 2), whereas other solvents provided only trace amounts of 3aa with unexpected 1,4-diphenylbuta-1,3-diyne as the major product by the homocoupling of 1a (entries 3-6). An extensive screening of nitrogen sources (entries 7-11), ligands (entries 12-16), [18] temperature (entries 17 and 18), copper loading (entry 19), additives (entries 20 and 21), and the atmosphere (entries 22 and 23) revealed that the use of two equivalents of Cu(NO 3 ) 2 ·3 H 2 Oinbenzonitrile at 60 8 8Cunder nitrogen atmosphere using tert-butylnitrile (2.0 equiv) as an additive provides the most suitable conditions and afforded 3aa in 83 %yield.…”
Section: Methodsmentioning
confidence: 99%
“…If dimethyl ether was used (with even greater solubilizing power) the rate of reaction appeared to increase (more rapid color changes), but not the isolated yield. Future efforts towards fluorinated metallocenes might benefit from recent developments in transition metal-catalyzed fluorinations (for example, from phenols, 22 aryl triflates, 23 stannanes, 24 boronic acids, 25 silanes 26 or iodides 27 ). 28 As with FcCl and fcCl 2 , aqueous FeCl 3 was used to remove FcH and FcH/FcF impurities from FcF and fcF 2 , respectively (Table 1).…”
mentioning
confidence: 99%
“…Pyridines substituted with chlorine-or methyl groups also afford good product yields (43 and 44). Quinolines, and pyrazine derivatives also render good yields of ortho-fluorine substituted products (46)(47)(48)(49), as is the case for pyrimidine and pyridazine substrates (50-54).…”
mentioning
confidence: 97%